Sustainability in Higher Education: a case study of the relationship teacher-student in the Administration course of FCAP/UPE (Research, Society and Development, 2020)
The research in focus sought to portray the understanding of academics about their interactions with teachers, as well as distinguish the probable interference of this conception in its adequacy to undergraduate and, consequently, in the sustainability of higher education. Therefore, the data were collected through a questionnaire applied to a sample of 30 undergraduate students from the University of Pernambuco (UPE). The information collected from the students was submitted to simple statistical analysis, and five factors of the teacher-student relationship were found that are capable of favoring or harming, depending on the situation, the university adaptation of these youngsters: 1- distinctions between high school and undergraduate teachers; 2- didactics and teacher training; 3- opening and stimulus; 4- university / personal interaction; and 5 - Responsibility given to the teacher in the training. The information indicated the relevance of teachers acting competently in the theoretical-didactic factors as well as in the interpersonal relationship. It is inferred that the teacher's function is not limited to the transmission of theoretical and technical knowledge of the profession.